2017
DOI: 10.1016/j.lwt.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of yoghurt with insoluble dietary fiber from triticale – A sensory perspective

Abstract: Please cite this article as: Tomic, N., Dojnov, B., Miocinovic, J., Tomasevic, I., Smigic, N., Djekic, I., Vujcic, Z., Enrichment of yoghurt with insoluble dietary fiber from triticale -A sensory perspective, ABSTRACT:27 Fortification of fermented dairy products with insoluble dietary fiber is an interesting way to 28 increase consumers' fiber intake. The objective of this study was to evaluate the sensory 29 characteristics and consumer acceptance of low-fat unsweetened yoghurt, fortified at levels of 30 15 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 20 publications
2
39
0
4
Order By: Relevance
“…As both fiber and yogurt are well known for their beneficial health effects, together will constitute a functional food with commercial applications.The results of Hashim et al (2009) are also corroborated, since 1.32% oat fibers addition improved the body and texture of unsweetened yogurt and decreased the overall flavour quality. Tomic et al (2017) found that addition of fibers from different sources (soy, rice, oat, corn, and sugar beet), at the level of 1.32%, in general led to lower overall flavor and texture scoresa grainy flavour and a gritty texture were intense in all samples except in those made with oat fiber. However, fiber size is also an important factor in yogurt formulation because of their impact on general acceptance.…”
Section: The Effect Of the Fibers Addition On The Sensorial Propertiementioning
confidence: 92%
See 1 more Smart Citation
“…As both fiber and yogurt are well known for their beneficial health effects, together will constitute a functional food with commercial applications.The results of Hashim et al (2009) are also corroborated, since 1.32% oat fibers addition improved the body and texture of unsweetened yogurt and decreased the overall flavour quality. Tomic et al (2017) found that addition of fibers from different sources (soy, rice, oat, corn, and sugar beet), at the level of 1.32%, in general led to lower overall flavor and texture scoresa grainy flavour and a gritty texture were intense in all samples except in those made with oat fiber. However, fiber size is also an important factor in yogurt formulation because of their impact on general acceptance.…”
Section: The Effect Of the Fibers Addition On The Sensorial Propertiementioning
confidence: 92%
“…Several studies reported prebiotic fortification by adding dietary fibers in yogurt. Consumption of highfiber yogurt may prevent or reduce obesity, diabetes, cancer, hypercholesterolemia, gastrointestinal disorders, colonic diverticulosis and constipation, ulcerative colitis, hyperlipidemia, hypertension, coronary artery disease, but also promote intestinal microflora and gastrointestinal immunity (Dello Staffolo, Sato, & Cunha, 2017;Dhingra, Michael, Rajput, & Patil, 2012;Hoppert et al, 2013;Ramirez-Santiago et al, 2010;Sah, Vasiljevic, McKechnie, & Donkor, 2016;Tomic et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Fortifying yogurt or dairy products with fiber is of increasing interest in creating functional foods with health benefits and improving their functionality (Gahruie, Eskandari, Mesbahi, & Hanifpour, ). Fortification is achieved by adding one or more essential nutrients to foodstuff, usually to prevent or correct deficiencies and enhance the nutritional value (Tomic et al, ). Yogurts are commonly fortified with various fruits, fruit seed extracts, and fibers, to enhance their health benefits (Kiros, Seifu, Bultosa, & Solomon, ).…”
Section: Introductionmentioning
confidence: 99%
“…The application of plant materials improves organoleptic and phisico-chemical parameters of bread [3][4][5][6], pasta [7][8][9] and yogurt products [10][11][12].…”
Section: Introductionmentioning
confidence: 99%